Peran Perempuan Dalam Mendukung Perekonomian Keluarga Pada Kegiatan Pariwisata Di Daerah Perbatasan - Veneranda Rini Hapsari; Usman Usman (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the role of women in supporting the family economy in tourism activities in border areas. The research method used is descriptive qualitative with research data obtained in the form of primary data namely observations, interviews and documentation as well as data in the form of journals and other supporting data related to research. The results obtained from this study are the potential of women in supporting tourism development such as in terms of providing culinary management, providing entrance tickets and bookkeeping in ticket administration and participation in managing homestays that have been provided in the tourist village.